The The Entrepreneurial Ecosystem, the Approach to Developing High Growth Oriented Enterprises: A Literature Review about the Entrepreneurial Ecosystem Situation in Malawi - James Gabriel Chilita (International Journal of Economics, Commerce, and Management, 2024)
Entrepreneurship is strongly being touted as the way out of underdevelopment in low income countries. Joblessness, poverty and social instability are some of the main issues that have haunted least developed countries since the end of colonialism, however, political independence without economic freedom is not freedom at all. There are fears that nations may fail due to underdevelopment and high levels of unemployment. Studies have been conducted elsewhere and in Malawi too about how the SMEs sector has been performing over the years and results show that the performance has not been encouraging at all. Nevertheless, the search still is on regarding how best developing countries in general and Malawi in particular can utilise the models such entrepreneurial ecosystems that are working well in developed economies to try to change the local fortunes. The findings of the studies done locally compared to those done in developed economies have shown that Malawi is not doing well at all more especially policy wise. The Government is supporting MSMEs wholesale without properly scrutinizing the business that are high growth oriented because it lacks such a policy. The study based on literature review hence recommends appropriate steps that can address the lack of positive dividends from the funds that are being invested in these underachieving MSMEs.